2015
DOI: 10.1175/jhm-d-14-0042.1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Precipitation Downscaling for Hydrologic Applications Using WRF 4D-Var Data Assimilation: Implications for GPM Era

Abstract: The objective of this study is to develop a framework for dynamically downscaling spaceborne precipitation products using the Weather Research and Forecasting (WRF) Model with four-dimensional variational data assimilation (4D-Var). Numerical experiments have been conducted to 1) understand the sensitivity of precipitation downscaling through point-scale precipitation data assimilation and 2) investigate the impact of seasonality and associated changes in precipitation-generating mechanisms on the quality of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…Both the sharp decreases in ME, RE, and RMSE from CTL1-2 to CTL3-4 ( Figure 9a) and the evident BIAS value much closer to 1 (Figure 9b) demonstrated a better WRF performance for event N than that for event A. This finding is consistent with that concluded by Lin et al, [42], where they found that the WRF model was relatively harder to use when forecasting convective and dominant precipitation events than precipitation events caused by extratropical cyclones.…”
Section: Wrf Sensitivity To Different Rainfall Events Forcing Data supporting
confidence: 90%
“…Both the sharp decreases in ME, RE, and RMSE from CTL1-2 to CTL3-4 ( Figure 9a) and the evident BIAS value much closer to 1 (Figure 9b) demonstrated a better WRF performance for event N than that for event A. This finding is consistent with that concluded by Lin et al, [42], where they found that the WRF model was relatively harder to use when forecasting convective and dominant precipitation events than precipitation events caused by extratropical cyclones.…”
Section: Wrf Sensitivity To Different Rainfall Events Forcing Data supporting
confidence: 90%
“…An error model to quantify uncertainty in fine-resolution precipitation products for satellite hydrology was proposed by Maggioni et al (2014) and Wright et al (2017). Lin et al (2015) developed a framework for dynamical precipitation downscaling through assimilating 6 h National Centers for Environmental Prediction (NCEP) Stage IV data using the Weather Research and Forecasting (WRF) four-dimensional (4D)-Variational system. This physically based downscaling methodology can be considered as a proof of concept for the downscaling of fine-scale GPM precipitation observations.…”
Section: Inputs To Hydrological Modellingmentioning
confidence: 99%
“…The hydrological modelling driven by the in situ observed and remotely sensed precipitation often span periods as long as several decades once the data are available [71,72]. In contrast, the time span of the hydrological modelling driven by the NWP-predicted precipitation is much shorter, as an NWP model commonly demands vast computational resources and computing time, particularly when it applies data assimilation and runs at a very fine grid spacing of 1 km [73][74][75][76]. Thus, to compare the effectivenesses of these different precipitation datasets on hydrological modelling, we focused our study on one short-term rainfall-runoff process and used it as a case study over the WJB watershed.…”
Section: Study Periodmentioning
confidence: 99%